Applying behavioural economics to international development policy - C. Leigh Anderson; Kostas Stamoulis (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2006)
Many development policies and programmes are premised on a traditional economic model of rationality to predict how individuals will respond to changes in incentives. Despite the emphasis of these programmes on poverty reduction, economists and the development community in general are still unable to fully understand how the poor make decisions, especially under uncertainty and over time. Individuals avail themselves less than predicted in health programmes, participate less than expected in market opportunities, under or over insure themselves, and make short-run decisions that are inconsistent with their long-run welfare. The rise and fall of different descriptive models and paradigms of poor household behaviour can partly be attributed to this limited understanding. More helpful answers may lay within behavioural economics, that these insights are particularly important for poor populations, and that they can improve the future design, implementation and subsequent effectiveness of development programmes. Behavioural economics is an approach that rigorously combines the insights of psychology and economics to try to better understand and predict human decision making. Empirical evidence is helping us learn, for example, how cognitive limitations, fairness, loss aversion, framing of choices, variable discount rates, and the qualitative dimensions of risk—such as proximity and control—affect decision making. The regularity of many of these anomalies suggests that these behaviours are anomalous only to traditional models, but that they may otherwise be the norm.
Keywords: D80; O12; 330; behavioural economics; policy; Verhaltensökonomik; Entwicklungshilfe